Coronectomy of Deeply Impacted Lower Third Molar: Incidence of Outcomes and Complications after One Year Follow-Up - Jimoh Olubanwo Agbaje; Guido Heijsters; Ahmed Sobhy Salem; Sarah Van Slycke; Serge Schepers; Constantinus Politis; Luc Vrielinck (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of present study was to assess the surgical management of impacted third molar with proximity to the inferior alveolar nerve and complications associated with coronectomy in a series of patients undergoing third molar surgery.